SYNTHESIS, BIOLOGICAL EVALUATION, MOLECULAR MODELING, AND DOCKING STUDIES OF CIPROFLOXACIN DERIVATIVES - Jena, Pradip K.; Pathak, Ashish K.; Sahu, Susanta K.; Tripathy, Swayansiddha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Ciprofloxacin, a fluoroquinolone analogue has activity against a wide range of Gram-negative and Gram-positive microorganisms by inhibiting the enzymes topoisomerase-II (DNA-gyrase) and topoisomerase-IV which are required for bacterial DNA replication, transcription, repair, and recombination. A series of ciprofloxacin Schiff bases were synthesized (1a-j) via >C=N- linkage by reacting ciprofloxacin with various primary amines through nucleophilic addition reaction in the presence of glacial acetic acid and were characterized on the basis of infrared, nuclear magnetic resonance, mass spectrometry, and elemental analysis techniques. In the present investigation, we screened ciprofloxacin Schiff bases based on a better Docking simulation with QRDR-A. The compound 1g, 1b and 1d resulted in a dock score of −154.82, −145.27 and −144.32 kcal.mol−1 ranked first, second, and third, respectively, and the compound 1g along with 1c, 1f, and 1j also interacted with Asp87. It was found that 1a, 1d, and 1e induced marked influence on Gram-negative and Gram-positive antibacterial activity. The compound 1j shows potent antifungal activity against Aspergillus niger and Candida albican. The compound 1g, shows an excellent anti-tubercular activity. The correlation between experimental data (minimum inhibitory concentration) versus docking score displayed 0.93 r2, which suggests that parameters for docking simulation are good in reproducing experimental orientation of these compounds. From the observed result, the analogs of ciprofloxacins are suggested to be potent inhibitors with sufficient scope for further exploration. Keywords: DNA-gyrase, Schiff bases, Docking, Molecular modeling.